Performance of Satuan PAUD Sejenis Managers through Managerial and Supervision Capability analysis - Sri Wahyuni; Erick Maison Putra; Mohammad Fauziddin (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to analyze the effect of managerial and supervisory abilities on the performance of satuan PAUD sejenis managers. The population in this study were all managers of satuan PAUD sejeniss throughout the city of Pekanbaru, amounting to 35 people, with a total sampling technique of sampling. This research method uses a descriptive and correlational analysis approach with research analysis tools, namely multiple linear regression. The results showed that partially: managerial ability affects the performance of managers of satuan PAUD sejeniss in Pekanbaru City. From the significance of the t test, Supervision has an effect on the performance of satuan PAUD sejenis Managers in Pekanbaru City. The two variables have an influence on the performance of satuan PAUD sejenis managers in Pekanbaru city with F count (66,812) greater than F table (2,911) with Sig. (0.000) smaller than 0.05